Liver disease and outcomes among COVID-19 hospitalized patients- a systematic review and meta-analysis (2020)
Introduction and Objectives: The coronavirus disease 2019 (COVID-19) pandemic has been a challenge globally. In severe acute respiratory syndrome (SARS) epidemic 60% of patients had hepatic injury, due to phylogenetic similarities of the viruses it is assumed that COVID-19 is associated with acute liver injury. In this meta-analysis, we aim to study the occurrence and association of liver injury, comorbid liver disease and elevated liver enzymes in COVID-19 confirmed hospitalizations with outcomes. Materials and Methods: Data from observational studies describing comorbid chronic liver disease, acute liver injury, elevated aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels and outcomes of COVID-19 hospitalized patients from December 1, 2019, to June 30, 2020 was extracted following PRISMA guidelines. Adverse outcomes were defined as admission to intensive care unit (ICU), oxygen saturation <90%, invasive mechanical ventilation (IMV), severe disease and in-hospital mortality. Odds ratio (OR) and 95% confidence interval (95%CI) were obtained. Results: 24 studies with 12882 confirmed COVID-19 patients were included. Overall prevalence of CMCLD was 2.6%, COVID-19-ALI was 26.5%, elevated AST was 41.1% and elevated ALT was 29.1%. CM-CLD had no significant association with poor outcomes (pooledOR:0.96;95%CI:0.71–1.29; p=0.78). COVID-19-ALI (1.68;1.04–2.70; p=0.03), elevated AST (2.98;2.35–3.77; p<0.00001) and elevated ALT (1.85;1.49–2.29; p<0.00001) were significantly associated with higher odds of poor outcomes. Conclusion: Our meta-analysis suggests that acute liver injury and elevated liver enzymes were significantly associated with COVID-19 severity. Future studies should evaluate changing levels of Journal Pre-proof biomarkers amongst liver disease patients to predict poor outcomes of COVID-19 and causes of liver injury during COVID-19 infection